PENATAAN KAMPUNG GUJI BARU DENGAN KONSEP KONSOLIDASI TANAH VERTIKAL - Rani Rachmasari; Suryono Herlambang; Suryadi Santoso (Jurusan Arsitektur dan Perencanaan, 2021)
Infrastructure Development The West Jakarta Administration has several plans, such as a plan to develop an activity center system that supports activity services and as a spatial structure builderGuji Baru Village will be improved with the Vertical Land Consolidation Concept, because this village has conditions that do not meet the requirements to be a good area, have irregular land, with land consolidation this village can be reorganized into a regular area complete with infrastructure, so that achieve optimal land use. The concept of land consolidation can systematically combine scattered and irregular land according to spatial planning, distribute existing consolidated land to landowners proportionally, regulate the form and layout of ownership parcels, increase economic value through the provision of environmentally friendly facilities and infrastructure. adequate on land donated by the owner. This concept has the principle of Cost & Benefit Sharing to the community and related stakeholders such as the government and developers. Land readjustment in the concept of Vertical Land Consolidation as a Multipurpose Technique can provide a number of benefits in urban development, including land assembly or consolidation, government land acquisition for public purposes, infrastructure development, legal implementation, fair distribution of costs and benefits, registration Land analysis, and timely land development. This study aims to implement improvements to the Guji Baru slum in order to create a good living environment according to the spatial plan, applying the concept of Vertical Land Consolidation. Key Word: GTRA; Vertical Land Consolidation, Village ImprovementAbstrakPengembangan Infrastruktur Kota Administrasi Jakarta Barat memiliki beberapa rencana seperti rencana pengembangan system pusat kegiatan yang menunjang pelayanan kegiatan dan sebagai pembentuk struktur ruang. Kampung Guji Baru akan diperbaiki dengan Konsep Konsolidasi Tanah Vertikal, karena kampung ini memiliki kondisi yang kurang memenuhi syarat untuk menjadi kawasan yang baik, memiliki lahan yang tidak teratur, dengan konsolidasi lahan maka kampung ini dapat ditata kembali menjadi kawasan yang teratur lengkap dengan prasarana, agar tercapai penggunaan lahan yang secara optimal. Konsep Konsolidasi Tanah dapat menggabungkan secara sistematis lahan yang berpencar-pencar dan tidak teratur disesuaikan dengan tata ruang, mendistribusikan lahan yang telah ada dikonsolidasikan kepada pemilik lahan secara proporsional, mengatur bentuk dan tata letak persil kepemilikan, meningkatkan nilai ekonomis melalui pengadaan sarana dan prasarana lingkungan yang memadai diatas lahan yang disumbangkan oleh pemilik. Konsep ini memiliki prinsip Cost & Benefit Sharing kepada masyarakat maupun stakeholder terkait seerti pemerintah dan developer. Penyesuaian kembali lahan dalan konsep Konsolidasi Tanah Vertikal sebagi Teknik multiguna dapat memberikan sejumlah manfaat dalam pembangunan perkotaan, termasuk perakitan atau konsolidasi tanah, pembebasan tanah pemerintah untuk tujuan umum, pembangunan infrastruktur, implementasi secara resmi, pembagian baiya dan manfaat yang adil, pendaftaran Analisa tanah, dan pengembangan tanah tepat waktu. Penlitian ini bertujuan untuk menerapkan perbaikan kampung kumuh Guji Baru agar tercipta lingkungan hidup yang baik sesuai rencana tata ruang, menerapkan konsep Konsolidasi Tanah Vertikal.